COMPORTAMENTO DE BOVINOS CONFINADOS RECEBENDO DIETAS COM DIFERENTES ADITIVOS - CORRÊA, Matheus Simão (matheuscorrea1084@hotmail.com; FERNANDES, Henrique Jorge; CANUTO, Nelson Guimarães Dantas (ANAIS DO ENIC, 2023)
-